Comparison of communication skill between railroad crossing guards - Dhina Setyo Oktaria (Jurnal Kajian Komunikasi, 2021)
Railroad Crossing Guard, commonly known as Penjaga Perlintasan Kereta Api (PJL), has a task in safeguarding the railroad crossing. In carrying out their task, PJL needs to communicate with other PJL and Train Dispatcher (PPKA) in the working area. Therefore, communication plays a critical role in the safety aspect. In 1987, the worst train accident happened in Indonesia’s history of railways, which was caused by miscommunication as the main factor of this accident. This study aims to improve communication skills for all PJL staff in Indonesia to achieve safety at railroad crossings. This study used primer data obtained from questionnaires distributed to 97 PJL individuals under Transportation Department (Dishub) and 97 PJL individuals under PT KAPM. Nowadays, PJL in Indonesia is under Dishub and PT KAPM. The sample was determined using Lemeshow’s formula because the number of subjects from previous studies was unknown or data on the exact number of all PJL in Indonesia was unavailable. Data were analyzed using descriptive and inferential statistics with the Man Whitney U test. PJL under the Transportation Agency and PJL under PT KAPM did not understand the importance of recording communication when maintaining a railroad crossing. The Mann-Whitney U test inferential statistics analysis indicates that the hypothesis was accepted, namely differences in communication skills between PJL under Dishub and PJL under PT. KAPM. The average ranking value was obtained from the total comparison value of all variables from PJL of Dushub and PJL of PT KAPM, with the Mann- Whitney U test results was 79.90 and the average ranking value of PJL under PT. KAPM was 113.10.